Continued Decline of Aqueous Interleukin-8 After Multiple Intravitreal Injections of Ganciclovir for Cytomegalovirus Retinitis - Wang, Bin (Mary Ann Liebert, Inc., 2014)
Purpose: To evaluate the relationship between aqueous inflammation cytokines and cytomegalovirus (CMV) particles in patients with cytomegalovirus retinitis (CMVR), and evaluate the changes in aqueous inflammation cytokines during multiple intravitreal injections of antiviral drugs for CMVR. Methods: There were 10 patients (12 eyes; 16 courses of treatment per eye) who underwent continued intravitreal ganciclovir or foscarnet for treatment of CMVR. Before each intravitreal injection, 50–100 μL of aqueous humor was removed and sent to the laboratory to examine the concentration of the CMV DNA load by using polymerase chain reaction and to examine the concentration of interleukin (IL)-1β, IL-6, IL-8, IL-10, tumor necrosis factor (TNF)-α, and IL-12p70 using a cytometric bead array. Results: A Kendall correlation test showed that the concentration of the CMV DNA load in the aqueous humor was significantly associated with the aqueous level of IL-6 (P<0.001, r=0.327) and IL-8 (P<0.001, r=0.381), but not significantly associated with IL-1β, IL-10, IL-12p70, and TNF-α. The boxplots showed that the concentration of the aqueous CMV DNA load, IL-8 and IL-10 continuously declined after multiple intravitreal injections of antiviral drugs, and the decline trend of IL-8 was most remarkable. IL-1β, IL-10, TNF-α, and IL-12p70 were negative in some of the aqueous levels of CMVR patients throughout the course of treatment (25.0%–62.5%). Conclusions: Our study showed that IL-8 was significantly associated with the aqueous level of CMV copies and continuously declined during a course of treatment that involved multiple intravitreal injections of antiviral drugs. IL-8 may be considered a good quantitative laboratory indicator of the recovery of CMVR.